ASXL2 mutated myelodysplastic syndrome in a novel germline G6b variant. (2022) - Qu, Shiqiang; Zhang, Donglei; Xu, Zefeng; Jia, Yujiao; Qin, Tiejun; Pan, Lijuan; Cai, Wenyu; Zhang, Yudi; Gale, Robert Peter; Xiao, Zhijian
Abstract: The 2016 revised World Health Organization classification identified myeloid neoplasms with germline predisposition as a new diagnostic category. Germline loss-of-function mutations in G6b (G6b-B, C6orf25 or MPIG6B) are associated with congenital macro-thrombocytopenia with focal myelofibrosis, a rare autosomal recessive disease. It is unclear whether germline G6b variants increase the risk of developing a myeloid neoplasm. Here we describe an adult with Myelodysplastic syndromes and a homozygous germline G6b mutation who achieved hematopoietic reconstitution by hematopoietic stem cell transplantation. As far as we know, this is the first report of adult Myelodysplastic syndromes with germline G6b homozygous variant in the literatures.